Wideband and non‐dispersive wavelet transmission using leaky lens antenna. Issue 5 (1st February 2013) - Vakili, I.; Ohlsson, L.; Gustafsson, M.; Wernersson, L.‐E.
Abstract : An ultra‐wideband, non‐dispersive leaky lens antenna system for impulse applications has been designed, fabricated and characterised. An in‐house wavelet generator is connected to the antenna to transmit 100 ps‐long square pulses with centre frequencies at 45, 60 and 75 GHz. It is shown that the leaky lens antenna has negligible distortion and preserves the pulse shape generated by the millimetre‐wave pulse generator.